2000
DOI: 10.1002/(sici)1099-0461(2000)14:3<131::aid-jbt2>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of xenobiotic metabolism and oxidative stress in chronic streptozotocin-induced diabetic rats fed with Momordica charantia fruit extract

Abstract: ABSTRACT:We studied the long-term effects of streptozotocin-induced diabetes on tissue-specific cytochrome P450 (CYP) and glutathione-dependent (GSHdependent) xenobiotic metabolism in rats. In addition, we also studied the effect of antidiabetic Momordica charantia (karela) fruit-extract feeding on the modulation of xenobiotic metabolism and oxidative stress in rats with diabetes. Our results have indicated an increase (35-50%) in CYP4A-dependent lauric acid hydroxylation in liver, kidney, and brain of diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
62
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 37 publications
9
62
0
Order By: Relevance
“…Conjugating the glutathione to a wide range of electrophiles, Glutathione S-transferases also reveal diverse response to lots of chemicals and oxidative stress in the normal and disease conditions as diabetes mellitus [32]. Our data also demonstrated that, excessive oxidative stress occurred in the liver due to diabetes mellitus, resulted in the down regulation of the expression GST-Mu gene.…”
Section: Discussionsupporting
confidence: 53%
“…Conjugating the glutathione to a wide range of electrophiles, Glutathione S-transferases also reveal diverse response to lots of chemicals and oxidative stress in the normal and disease conditions as diabetes mellitus [32]. Our data also demonstrated that, excessive oxidative stress occurred in the liver due to diabetes mellitus, resulted in the down regulation of the expression GST-Mu gene.…”
Section: Discussionsupporting
confidence: 53%
“…At maturity, the fruit splits into three irregular valves that curl backwards and release numerous reddish-brown seeds. Biological actions of various extracts of the plants or its constituents include antidiabetic (Ahmed et al, 1998;Mastuda et al, 1999;Raza et al, 2000), anti ulcerogenic (Gürbüz et al, 2000), antimutagenic (Guevara et al, 1990), antioxidant (Scartezzini & Speroni, 2000), anti-tumour (Lee-Huang et al, 1995a), immunomodulatory (Spreafico et al, 1983). Two proteins known as α -and β -monorcharin which are present in the seeds, fruits and leaves have shown to inhibit the human immune deficiency virus (HIV) in vitro (Zhang, 1992;LeeHuang et al, 1995b).…”
Section: Introductionmentioning
confidence: 99%
“…9 Overexpression of CYP2E1 is of direct importance to human health and is associated with a range of diseases, including diabetes mellitus, alcoholic liver disease, and cancer. [10][11][12] The expression level of CYP2E1 increases significantly in heart tissues in humans under ischemia; mice, rats, and dogs with dilated cardiomyopathy (DCM); and spontaneously hypertensive rats. [13][14][15][16][17][18] The overexpression of CYP2E1 is associated with several cellular markers of oxidative stress, as well as with decreased viability as a result of both necrosis and apoptosis.…”
mentioning
confidence: 99%